PERAN PENYULUH PERTANIAN DALAM MENINGKATKAN PRODUKSI TANAMAN SAYURAN PADA KELOMPOK TANI NEKMESE DI DESA KESETNANA KECAMATAN MOLLO SELATAN KABUPATEN TIMOR TENGAH SELATAN - Hurint, Jefri Pati; Nainiti, Selfius P.N.; Bernadina, Lika (Undana Press, 2024)
This study aims to determine the role of agricultural extension agents in increasing vegetable crop production. The next objective is to determine the efforts made by extension agents to increase vegetable crop production and the production problems faced by farmers. The research was conducted in Kesetnana Village, South Mollo District, South Central Timor District. Measurements use an ordinal scale and are quantified with a Likert scale. Analysis of the role of extension agents used quantitative descriptive analysis by comparing the percentage value of achieving the maximum score of the average score with a reference table. Meanwhile, to find out the efforts made by extension workers to increase vegetable crop production and production problems faced by farmers with qualitative descriptive analysis. Based on the results of data analysis, it was found that the average score of the agricultural instructor's role as a facilitator in increasing the production of vegetable farming in the Nekmese Farmer Group averaged 2.31 (77.08%). The average score of the role of agricultural extension as a motivator is 2.52. (84.02%) and the average score of the role of extension workers as educators is 2.48 (82.64%). This shows that the role of agricultural extension workers as motivators and educators in improving vegetable farming in the Nekmese farmer group is classified as